'Making every contact count': Evaluation of the impact of an intervention to train health and social care practitioners in skills to support health behaviour change. (February 2016) - Lawrence, Wendy; Black, Christina; Tinati, Tannaze; Cradock, Sue; Begum, Rufia; Jarman, Megan; Pease, Anna; Margetts, Barrie; Davies, Jenny; Inskip, Hazel; Cooper, Cyrus; Baird, Janis; et al.
A total of 148 health and social care practitioners were trained in skills to support behaviour change: creating opportunities to discuss health behaviours, using open discovery questions, listening, reflecting and goal-setting. At three time points post-training, use of the skills was evaluated and compared with use of skills by untrained practitioners. Trained practitioners demonstrated significantly greater use of these client-centred skills to support behaviour change compared to their untrained peers up to 1 year post-training. Because it uses existing services to deliver support for behaviour change, this training intervention has the potential to improve public health at relatively low cost.